148k views
1 vote
This got me confused but can somebody please tell me what the answer is to: 7(2x - 3) = 14x + 7​

User Ethan C
by
5.2k points

2 Answers

4 votes

Answer:

There is no x that satisfies the condition.

Explanation:

7(2x - 3) = 14x + 7

14x - 21 = 14x + 7

-21 = 7

contradiction

User Mobility
by
5.4k points
6 votes

Answer:

14x-21=14x +7

x cancels all out which leaves with just

28

User Tigrish
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.